Peer group support and motivational interviewing interventions impact parents’ behavior in preventing tuberculosis among children - Rahmawati, Apriana; Utomo, Budi; Makhfudli, Makhfudli; Wulandari, Shenda Maulina; Abdullah, Khatijah Lim (Palembang MediRose Publisher, 2024)
Background: Tuberculosis (TB) serves as a key indicator for assessing public health at the population level. The infection of children and toddlers with TB often stems from the lack of involvement by family members in adhering to proper hygiene practices aimed at preventing TB transmission.Objective: This study aimed to assess the impact of peer group support and motivational interviewing on parental behaviors in preventing TB transmission among children residing in the same household as a TB patient. Methods: Employing a quasi-experimental design (pre-post test with a single group), this study involved 30 parents selected through accidental sampling. The independent variables included peer group support and motivational interviewing, while the dependent variable was parental behavior concerning TB prevention in children. Data collection utilized a questionnaire assessing parents’ behaviors in preventing TB in children, which was then analyzed using the paired t-test.Results: The implementation of peer group support and motivational interviewing significantly influenced the enhancement of parental behaviors in preventing TB in children (p < 0.001).Conclusion: Both peer group support and motivational interviewing demonstrated their efficacy in altering parental behavior to prevent TB in children residing with a TB patient. These interventions could be effectively incorporated by nurses to complement ongoing tuberculosis treatment therapies.